APLIKASI PLASMA DINGIN UNTUK PERAWATAN LUKA - NASRUDIN, NASRUDIN; PRIBADI, PRASOJO (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: This study aims to determine the effect of cold plasma treatment for 7 days on wound healing in female Sprague Dawley ratsMethods: In studies using an experimental design that is 15 test animals were divided into three groups , namely positive control ( povidone iodine ) , positive control ( no treatment ) , cold plasma treatmentResults: wound healing descriptive operates on cold plasma treatment group there is an increased effectiveness of the wound, operating while statistics can be inferred no difference significant wound healing effectiveness cold plasma treatment between the negative controlConclusion: Aapplication of cold plasma had no effect wound healing